Lymphocyte Subpopulations in Pulmonary Tuberculosis Patients - Figen Deveci; H. Handan Akbulut; Ilhami Celik; M. Hamdi Muz; Fulya İlhan (Hindawi Limited, 2006)
Protection against Mycobacterium tuberculosis is based on cell-mediated immunity, most importantly involving CD4+ and CD8+ T-cell subsets. The aim of this study was to evaluate CD4+ and CD8+ T-cell profiles and CD19+ and CD3-CD(16+56)+ populations in patients with pulmonary tuberculosis. CD4+ and CD8+ T cells, B-lymphocytes, and natural killer (NK) cells were evaluated in 75 active (APTB) and 25 inactive (IPTB) pulmonary tuberculosis cases and 20 healthy subjects (HCs). The results were compared at different stages of antituberculosis treatment in the APTB patients and also according to X-ray findings in the newly diagnosed APTB patients. The percentages of CD4+ T cells were significantly lower (P<.01) and those of CD3-CD(16+56)+ cells were significantly higher (P<.01) in APTB patients than in HCs. CD8+ T cells were significantly decreased (P<.05), and CD3-CD(16+56)+ cells were significantly increased (P<.01), in IPTB patients compared to HCs. The percentages of CD4+, CD8+, CD3-CD19+, and CD3-CD(16+56)+ cells showed no differences at different times of the antituberculosis regimen, and different stages of newly diagnosed APTB patients. APTB patients have a reduced percentage of circulating CD4+ T cells and an increased percentage of NK cells compared with healthy individuals. These cells could play important roles in the immune response to M tuberculosis infection.